Case Report: A case of reversible pulmonary bullae induced by camrelizumab: a new immune-related adverse event - Wang, Yun; Wang, Shaoshan; Li, Qin; Cui, Qihao; Song, Jiafu; Zheng, Hong (Frontiers in Immunology, 2025)
With the widespread clinical application of immune checkpoint inhibitors (ICIs), the treatment of lung squamous cell carcinoma (LUSC) has entered a new era, characterized by equal emphasis on precision medicine and immunotherapy. Among these, programmed cell death protein-1 (PD-1) inhibitors have demonstrated significant efficacy in prolonging patient survival. However, while immunotherapy provides substantial clinical benefits, it may also induce immune-related adverse events (irAEs). We report a case of a 74-year-old male with LUSC who developed reversible pulmonary bullae following camrelizumab treatment. The patient presented with a one-year history of cough. Chest CT revealed a right hilar mass (11×10cm) with pleural effusion. Histopathological analysis of EBUS-TBNA specimens confirmed squamous cell carcinoma. Comprehensive systemic evaluation established the diagnosis of right lung squamous cell carcinoma (cT4N3M1a, stage IVA). The patient received albumin-bound paclitaxel and carboplatin in combination with camrelizumab. During treatment, the patient developed a known immune-related adverse event, interstitial pneumonitis, as well as a previously unreported complication, pulmonary bullae. After discontinuation of camrelizumab and initiation of glucocorticoid therapy (methylprednisolone), the pulmonary bullae showed significant resolution. We believe that the formation of these reversible pulmonary bulla may be associated with two mechanisms. First, immune-mediated airway inflammation and mucus-induced airway obstruction. Second, microvascular or small pulmonary vessel thrombosis leading to localized ischemic injury, which may allow thrombi to enter the airway lumen. Both mechanisms may contribute to a “One-way valve” effect, resulting in alveolar overdistension and bulla formation. This case suggests that pulmonary bullae may represent a rare pulmonary irAE associated with camrelizumab. It provides new clinical insights into immune-related pulmonary complications and offers a valuable reference for the management of similar cases.